Exploring Styrofoam Box Consumer Preferences, Experiential Marketing Perspectives, and Their Impact on Purchase Decisions - Tasrik Hasrat; Budiandriani Budiandriani; Khairina Rosyadah (Vifada Management and Social Sciences, 2025)
Purpose: This study aims to analyze consumer preferences regarding the use of styrofoam box packaging as an alternative to wooden box packaging and to examine the influence of experiential marketing dimensions, including sensory, emotional, and cognitive elements, on perceived product quality and purchasing decisions. Research Design and Methodology: This research employed a quantitative explanatory approach using Structural Equation Modeling (SEM). Data were collected through a structured questionnaire distributed to 100 consumers using styrofoam box packaging. The analysis focused on examining the relationships among consumer knowledge, reference groups, perceived quality, perceived price, experiential marketing, and purchasing decisions. Findings and Discussion: The findings indicate that consumer knowledge, reference groups, perceived quality, perceived price, and experiential marketing have significant positive effects on purchasing decisions. In addition, styrofoam box packaging positively influences consumer purchase decisions due to its practicality, affordability, and ability to provide effective product protection compared to wooden box packaging. The study also demonstrates that experiential marketing plays an important role in strengthening consumer perceptions and enhancing product competitiveness. These findings contribute to the packaging and marketing literature by emphasizing the relevance of experiential marketing dimensions within SEM analysis in understanding consumer behavior toward alternative packaging solutions. Implications: The results provide practical insights for packaging manufacturers and marketers in developing innovative, cost-effective, and consumer-oriented packaging strategies. Future studies are recommended to explore additional variables, broader consumer segments, and comparative analyses with environmentally friendly packaging alternatives.